A simple action for a free fractional spin particle - Dalmazi, D. [UNESP]; Dutra, Alvaro de Souza [UNESP] (Elsevier, 1997)
By studying classical realizations of the sl(2, R-fraktur sign) algebra in a two dimensional phase space (q,π), we have derived a continuous family of new actions for free fractional spin particles in 2 + 1 dimensions. For the case of light-like spin vector (SμSμ = 0), the action is remarkably simple. We show the appearence of the Zitterbewegung in the solutions of the equations of motion, and relate the actions to others in the literature at classical level. © 1997 Elsevier Science B.V.